shelby1290
  • shelby1290
Determine the value(s) of k such that each trinomial is a perfect square. a) x^2 + 4x + k b) 4x^2 - 12x + k
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
misty1212
  • misty1212
two steps only
misty1212
  • misty1212
what is half of 4?
shelby1290
  • shelby1290
@misty1212 half of 4 is 2

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

shelby1290
  • shelby1290
what's next?
anonymous
  • anonymous
\[b^2-4ac=0\]
anonymous
  • anonymous
\[4^2-4(1)(k)=0\]
anonymous
  • anonymous
k=?
shelby1290
  • shelby1290
12?
anonymous
  • anonymous
Try again
shelby1290
  • shelby1290
4^2-4(1)(k) 16-4k=0 divide both sides by -4 k=-4
shelby1290
  • shelby1290
is that right?
anonymous
  • anonymous
\[16-4k=0 \\ \\ 16=4k \\ \\ k=?\]
shelby1290
  • shelby1290
k = 4 oops
shelby1290
  • shelby1290
thank you
shelby1290
  • shelby1290
now how about part b
anonymous
  • anonymous
Do the same for the next one \[4x^2 - 12x + k=0 \\ Using \\ ax^2+bx+c=0 \\ \\ b^2-4ac=0\]
anonymous
  • anonymous
\[(-12)^2-4(4)(k)=0\]
shelby1290
  • shelby1290
-144-16k=0 -144=16k divide both sides by 16 k=-9 ?
anonymous
  • anonymous
\[(-12)^2= (-12)(-12)=12 \times 12=144\]
anonymous
  • anonymous
k=9
shelby1290
  • shelby1290
oh i see it's because i didn't put (-12)^2 in brackets
shelby1290
  • shelby1290
thanks for the help though!

Looking for something else?

Not the answer you are looking for? Search for more explanations.